Exploring the Influence of Family Dynamics on Death Attitude among Elderly People: A Comparative Study of Chitwan and Jhapa District, Nepalrict, Nepal - Karki, Tej Bahadur; D’Mello, Laveena; Poudel , Gehanath; Ghimire , Mayanath; Neupane, Dasarath; Shrestha, Sajeeb Kumar; Mahat, Dipak (MultiTech Publisher, 2024)
This research examines the impact of living arrangements on death attitudes among elderly individuals in Nepal's Chitwan and Jhapa districts. A cross-sectional survey of 127 participants (79 in elder homes, 48 in their own homes) was conducted and analyzed using SPSS v.20. Significant differences in death attitudes were found based on living arrangements. Elder home residents showed greater acceptance of quick death, less fear, and viewed death more as relief from pain. They preferred dying in religious places, while those in their own homes preferred passing at home. Belief in reincarnation was higher among those living independently. The study reveals that living environments significantly influence elderly individuals' death attitudes, with elder home residents exhibiting more acceptance towards death. These findings suggest a need for tailored end-of-life care and support services that consider living arrangements and cultural contexts, contributing to the discourse on geriatric care in diverse settings.